The chancellery of the golden horde’s Khans - Z. Minnullin, A. Gatin, G. Gali, L. Abzalov, M. Gatin, R. Fakhrutdinov, B. Fakhrutdinov, D. Mustafina, (Opción, 2019)
This article provides an overview of the chancellery service of the Golden Horde via comparative qualitative research methods. As a result, the main work in the office was carried out by scribes - bitikchi. They prepared the decrees of the ruler, diplomatic messages, kept documents, were engaged in translation and financial and fiscal issues. The bitikchi should have mastered the Mongolian and Turkic languages and the Uigur script. In conclusion, the chancellery culture of UlusJuchi was at a high level of development and was able to ensure the effective management of such a large and powerful state.